“They Are Not Hard-to-Reach Clients. We Have Just Got Hard-to-Reach Services.” Staff Views of Digital Health Tools in Specialist Mental Health Services. - Bucci, Sandra; Berry, Natalie; Morris, Rohan; Berry, Katherine; Haddock, Gillian; Lewis, Shôn; Edge, Dawn (Frontiers in Psychiatry, 2019)
Background: Digital health products designed to help people with severe mental health problems appear to be feasible, acceptable and efficacious. The challenge facing the digital mental health field is implementing digital tools in routine service delivery. To date, there has been a paucity of qualitative research exploring staff views of digital health solutions in the context of mental healthcare. Engaging and involving frontline staff in the design and roll-out of new technology to improve utilisation is imperative for successful uptake and adoption of digital tools. The aim of the current study is to explore frontline staff views regarding the utility and appropriateness of using digital tools in the healthcare pathway for people accessing specialist secondary care mental health services. Method: Qualitative study using Framework Analysis was used with 48 mental health staff working in early intervention for psychosis services. Six groups comprising 5-10 Early Intervention Service staff members in each group were conducted across the Northwest of England. Robust measures were used to develop a stable Framework, including member checking, triangulation and consensus meetings. Results: Three themes were identified a priori: i) perceived barriers to adopting smartphone apps for early psychosis; ii) acceptability of digital health tools for early psychosis patients; iii) data security, safety and risk. Alongside exploring the a priori topics, one theme was generated a posteriori: iv) relationships. Conclusions: Staff working in specialist early intervention for psychosis services found digital tools on the whole acceptable in mental health service provision, but raised a number of concerns that will likely effect implementation of such systems into routine service delivery and practice. Thirteen recommendations are made in this paper as a result of the themes generated in these data. Implementing digital systems needs to be simple, uncomplicated and improve clinical workflows for staff rather than hinder and increase clinical workflows. Furthermore, organisational support with a clear plan for implementing technological innovations is required for successful adoption of digital systems. Consideration of staff views around digital systems is important if successful adoption and implementation of such systems are to occur.